Search for highly-ionizing particles in pp collisions at the LHC's Run-1 using the prototype MoEDAL detector. - Acharya, B..; Alexandre, J..; Benes, P..; Bergmann, B..; Bertolucci, S..; Bevan, A..; Bhattacharyya, R..; Branzas, H..; Burian, P..; Campbell, M..; Cecchini, S..; Cho, Y. M.; Montigny, M..; De Roeck, A..; Ellis, J. R.; El Sawy, M..; Fairbairn, M..; Felea, D..; Frank, M..; Hays, J..; Hirt, A. M.; Hung, P. Q.; Janecek, J..; Kalliokoski, M..; Korzenev, A..; Lacarrére, D. H.; Leroy, C..; Levi, G..; Lionti, A..; Margiotta, A..; Maselek, R..; Maulik, A..; Mauri, N..; Mavromatos, N. E.; Musumeci, E..; Mieskolainen, M..; Millward, L..; Mitsou, V. A.; Orava, R..; Ostrovskiy, I..; Ouimet, P.-P..; Papavassiliou, J..; Parker, B..; Patrizii, L..; Păvălaş, G. E.; Pinfold, J. L.; Popa, L. A.; Popa, V..; Pozzato, M..; Pospisil, S..; Rajantie, A..; Ruiz de Austri, R..; Sahnoun, Z..; Sakellariadou, M..; Sakurai, K..; Santra, A..; Sarkar, S..; Semenoff, G..; Shaa, A..; Sirri, G..; Sliwa, K..; Soluk, R..; Spurio, M..; Staelens, M..; Suk, M..; Tenti, M..; Togo, V..; Tuszyński, J. A.; Upreti, A..; Vento, V..; Vives, O.. (Tufts University. Tisch Library., 2022)
Springer Open.